Resistive and propulsive forces in wheelchair racing: a brief review - Silveira, Ricardo (2022)
Wheelchair racing is one of the most important sports in the Paralympics. The detailed analysis of all parameters is of great importance to achieve sporting excellence in this modality. In wheelchair racing, resistive and propulsive forces determine the movement of the athlete-wheelchair system. Most of propulsive forces are generated by the strength of individuals. As a result, strength levels play an important role in propelling the athlete-wheelchair system. Thus, the main objective of this study is to provide a set of methodologies to assess propulsive and resistive forces. The manuscript presents different methods and procedures, based on previous studies, that can be used for wheelchair racing athletes. Resistive forces in wheelchair racing can be evaluated by analytical procedures, experimental tests, and numerical simulations. Moreover, the strength of athletes' upper limbs to generate propulsion in wheelchair races can be assessed by dynamometry, one-repetition maximum, and medicine ball throw test. It may be that the tests presented may be useful to predict the strength and endurance of athletes' upper limbs. However, this competitive sport still presents a considerable gap in the Paralympics research. Currently, in Paralympic sport, evidence-based methodologies are lacking, making it an issue for athletes, coaches and researchers to support their work on scientific evidences.